From inflammatory activation to fibrotic remodeling: the central role of macrophage heterogeneity in frozen shoulder - Liang, Hao; Liu, Jianmin (Frontiers in Immunology, 2026)
Frozen shoulder (FS) is a condition primarily marked by chronic inflammation and progressive fibrosis of the glenohumeral capsule. Clinically, it presents with persistent shoulder pain and limited joint mobility, often leading to impaired upper limb function and reduced quality of life. In recent years, research on the molecular mechanisms of fibrosis in FS has deepened; however, there remains a lack of systematic focus on the dynamic regulation of the immune microenvironment, particularly the role of macrophage heterogeneity. The remarkable functional plasticity of macrophages allows them to play dual roles in inflammatory responses and tissue repair, with the sequential transformation of their phenotypes and functions potentially governing various stages of FS development. This review focuses on the dynamic evolution of macrophage function and polarization states during FS progression. This review systematically outlines the key roles of these cells in inflammatory responses, fibrosis progression, and their signaling interactions with fibroblasts. We systematically assessed the critical signaling networks that regulate macrophage recruitment and differentiation, emphasizing the core roles of the C-C motif chemokine ligand 2 (CCL2)/C-C chemokine receptor type 2 (CCR2) chemotactic axis and tissue mechanical signals in this process. Additionally, we explored how the synergy between immune signaling and mechanotransduction maintains the pathogenic activation state of macrophages, potentially forming a positive feedback loop for fibrosis. Targeting these upstream inputs holds promise as a potential intervention to disrupt the link between inflammation and fibrosis. A deeper understanding of the regulatory mechanisms governing macrophage heterogeneity will lay the foundation for developing more targeted therapeutic approaches for FS in the future.